APPLICATIONS AND COMPLICATIONS OF POLYURETHANE STENTING IN UROLOGY - Arshad, M; Shah, Shahzad S.; Abbasi, Muhammad H. (Journal of Ayub Medical College Abbottabad, 2006)
Background: As surgeons working in a developing country, we decided to review our experience with polyurethane stents instead of the more expensive ones on common urological procedures and analyzing our experience with respect to their usefulness versus their problems and outcome. Methods: This stusy was carried out at Armed Forces Institute of Urology, Rawalpindi and Combined Military Hospital, Kharian Cantonment, Pakistan through March 2002 through May 2004. During this period 342 of patients were operated requiring stent and 220 patients out of these had polyurethane as stent material for different urological operations. Results: Among the 220 patients who underwent polyurethane stenting, early complications included fever, infection, voiding symptoms while stent migration, encrustation and stent stiffness was encountered as later complications. Conclusion: The benefits of Polyurethane stents are its strength, versatility and low cost. Poor biodurability and biocompatibility only limit its use; these are reasonably effective in our setup but should only be used for short duration. Key words: Urology Stents, Polyurethane, Complications.